Perceptions on the Nexus between Water and Religion: A Christian Theological Perspective - Mahlalela, Linda; Khumalo, Mandla (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
Water plays a crucial role in societies and the universe as a whole. It creates and sustains life and, in the process, legitimizes social hierarchies. Water is used in several physical and non-physical ways, including in religious practices. However, there appear to be insufficient studies that try to ascertain the link between Water and religion. This study examined perceptions of the association between water and religion. It assessed water as a sacred resource in line with theological aspects, as being required in remembering God through spiritual rituals and practices, for He allows humanity and nature to flourish. The study also addressed the importance of conserving this resource. An interpretive and theological framework from the Christian perspective was used to understand this nexus. Further thematic analysis led to the identification of three main themes. Semi-structured interviews were carried out with 21 participants from the Christian faith. The results revealed that water is a sacred resource that is highly used in religion. It brings healing, sanctification, and consecration among users. Water also plays a pivotal role in baptism and spiritual rituals, and is also very helpful in improving the health of individuals. Water conservation, including rainwater harvesting, recycling, and the avoidance of water pollution, was recommended.